Fiscal Sustainability and Resource Mobilization in the Dominican Republic - Melhado Orellana, Oscar (IMF Working Papers; Working Paper ;, 2003)
This paper examines fiscal sustainability and resource mobilization in the Dominican Republic. The fiscal position appears to be sustainable, if resource mobilization is strengthened. If expenditure continues to rise (relative to GDP), without any further fiscal adjustment, indicators of sustainability would begin to deteriorate. It would be important to maintain an appropriate mix between additional financing and fiscal adjustment, in order that the future debt burden does not rise excessively.